Books and builders : a bibliographical approach to Irish eighteenth-century architecture - Casey, Christine (Trinity College (Dublin, Ireland). Department of History of Art and Architecture, 1992)
This study is an attempt to construct the bibIiographical dimension of Irish eighteenth-century architectural history. Irish newspapers of the period have been combed for publication notices and subscription proposals and a representative cross-section of contemporary book catalogues has been sifted for architectural titles. The combination of these methods serves to give a general picture of the literature being collected by Irish library owners and that which was being sold by the book trade. Another avenue of approach has been the analysis of Irish manuscript materials which display a clear reliance upon published architectural works. Several curious manuscript volumes compiled in Ireland during the course of the eighteenth century vividly illustrate the usage of architectural books and prints both by amateurs and professional architects. The bookish nature of these documents demonstrates more clearly than built architecture, the assimilation of published proto-types into Irish eighteenth-century design. Having established the type of literature which was published in Ireland and that which was in general circulation, it was then requisite to consider the individuals who bought, sold, wrote, read or perused architectural publications. Irish library owners, the booksellers of Dublin and a handful of Irish architects and authors serve to humanise an otherwise exclusively bookish history. Given the preliminary state of Irish biographical studies, lengthy research was necessary to determine the identity and position of many lesser figures in the contemporary building world who were associated in a variety of ways with architectural literature. Perhaps the most useful contribution of this study to the architectural history of the period and to Irish eighteenth-century studies in general, is the new information which it provides on contemporary patrons, lesser known architects, builders and critics. This information adds significantly to our understanding of contemporary architecture.
Keywords: History of Art and Architecture, Ph.D.; Ph.D. Trinity College Dublin